Protein profile of Acidithiobacillus ferrooxidans strains exhibiting different levels of tolerance to metal sulfates - Novo, MTM; Garcia, O.; Ottoboni, LMM (Springer, 2003)
Strains of Acidithiobacillus ferrooxidans exhibited differences in the inhibition of Fe(2+) oxidation in the presence of 250 mm of cadmium, zinc, and manganese sulfates in respirometric assays. Strains LR and I35 were practically not inhibited, whereas strains SSP and V3 showed significant inhibition (30-70%). Analysis by SDS-PAGE of total proteins from cells grown in the absence of metal sulfates showed different profiles between the more tolerant strains (LR and 135) and the more susceptible ones (SSP and V3). Total proteins of strains LR and V3 were also resolved by two-dimensional polyacrylamide gel electrophoresis (2-DE). A set of major proteins (40, 32, 22, and 20 kDa) could be identified only in the more tolerant strain LR. Our results show that protein profiles analysis could differentiate A. ferrooxidans strains that considerably differ in the tolerance to metal sulfates and present low genomic similarity as revealed by Random Amplified Polymorphic DNA (RAPD) data obtained previously in our laboratory.